Retrospective Analysis of Dermatological Diseases in Geriatric Patients During Dermatology Outpatient Department Visits - Gulhan Aksoy Sarac; Mehmet Ali Can Emeksiz; Onur Acar; Ersin Nazlıcan; Efsun Tanacan; Tufan Nayir (Mattioli1885, 2022)
Introduction: Elderly population is vulnarable to experience a great number of dermatological diseases thanks to the intrinsic and extrinsic process of aging. Objectives: The aim of this study is to retrospectively investigate the prevalence of dermatological diseases in geriatric patients, their distribution by age and gender, and to provide a reference for studies on aging and skin problems. Methods: In the present study, patients who reported to the dermatology outpatient clinic between January 1, 2019 and January 1, 2021 were evaluated retrospectively. As a result of examining the records of patients, 887 patients over the age of 65 who met the study protocol were included. Results: The three most common diseases in all geriatric patients were fungal infections, eczematous dermatitis, and pruritus. Fungal infections were frequent in males and the 65-74 ages group. In the males, the more frequent was precancerous lesions and malignant neoplasms, whereas in the females it was urticaria and adverse drug reactions. In the logistic regression model, the risk of fungal infection in geriatric patients was increased by being male (OR: 1.55 p=0.006) and being in the range of 65-74 years old (OR: 1.46 p=0.025). Male patients were at significantly higher risk for precancerous and malignant lesions (OR:2.81 p<0.001) and actinic keratosis (OR:3.26 p<0.001) in this disease group. Conclusions: Men are more vulnerable to life-threatening skin diseases. It is important to determine risk factors for individuals who are more sensitive to environmental factors in terms of increasing the quality of life and protection from diseases.